Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/md.0000000000013604
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in reporting versus rating of healthcare experiences

Abstract: Asians are reported to have poorer healthcare experience than non-Hispanic Whites (NHWs), but the sources of the differences are not understood. One explanation is Asian's reluctance to choose extreme responses in survey. We thus sought to compare NHW-Asian differences in responses to healthcare experience surveys when asked to report versus rate their experiences. Patients of an outpatient care system in 2013 to 2014 in the United States were studied. Patient experience surveys were sent after randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Since this study was limited by the participants recruited from a medical center in Taiwan, the generalization could be limited to the geographic area. Moreover, the Consumer Assessment of Healthcare Providers and Systems and the Press Ganey Medical Practice Survey revealed that Asian patients reported lower healthcare experience ratings than did Caucasian patients (Chung, Mujal, Liang, Palaniappan, & Frosch, 2018; Liao et al, 2020). Indeed, the cultural background of the participants concerning their illness and perception play an essential factor in the administration of health care.…”
Section: Discussionmentioning
confidence: 99%
“…Since this study was limited by the participants recruited from a medical center in Taiwan, the generalization could be limited to the geographic area. Moreover, the Consumer Assessment of Healthcare Providers and Systems and the Press Ganey Medical Practice Survey revealed that Asian patients reported lower healthcare experience ratings than did Caucasian patients (Chung, Mujal, Liang, Palaniappan, & Frosch, 2018; Liao et al, 2020). Indeed, the cultural background of the participants concerning their illness and perception play an essential factor in the administration of health care.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the relationship was modest (0.43 percentage point per each level in burnout scale) in part due to the ceiling effect in patient experience surveys. As variation in patient experience scores across organizations is known to be very small 23,53,54 and the variation across providers within an organization can be even smaller, the effect size observed here can be considered meaningful. Although the trends were in the same direction, the effects on access and the overall rating of the physician, after controlling for PCP workload, were not significant.…”
Section: Discussionmentioning
confidence: 80%
“…Response rates ranged from 15 to 20%, typical of patient experience surveys sent without financial incentives or reminders. 21,22 While response rates vary by patient demographics, e.g., older and non-Hispanic white individuals are more likely to respond, [23][24][25][26][27] potential bias due to low response rate at provider level, after adjusting…”
Section: Study Design/setting/participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Standardization of question wording and survey administration methods are designed to remove variables that may contribute to undesired variation. Nonetheless, studies have demonstrated variation in questionnaire responses due to race/ethnicity, 17 changes in language concordance, 18 or verbal tone. 19,20 A variety of common method biases exist with questionnaires and these are difficult to define and measure.…”
Section: Discussionmentioning
confidence: 99%